Mães de filhos com deficiência: histórias de superação com a terapia comunitária integrativa - Guerra, Camilla de Sena (2014)
It is a research with qualitative approach, where the Thematic Oral History was used to guide its operation. This study had the objectives of: Knowing the repercussions of wheels TCI in mothers of disabled child and experiencing situations of suffering; Highlighting the main signs of emotional distress experienced by these mothers; Identify the strategies most used by these mothers to face the emotional distress; Highlight the contributions of TCI for mothers of children with disabilities in view the importance of this care tool for this particular group; Reveal the contributions required in the life of the mother involved in the TCI in the care of children with disabilities.The place of study was the ADAT (Association of Handicapped Friends of Timbaúba-PE), located in the city of Timbaúba-PE. The empirical material was produced based on the performance of 12 discussion groups of ICT in the institution, where after the intervention that in the case of the study was the ICT performed, the interview was done with the mothers who participated of the discussion groups assiduously. The interview was performed with six contributors, and the product of this material was discussed based on the interpretative thematic analysis, that subsided the construction of three big thematic axis, as it follows respectively: From the dream of the perfect child the experience of being mother of a disabled child; Strategies of combat to take care of the disabled child; The ICT as empowering of bonds, sharing and space of the empowering. Such axes stimulate the discussion based on the confrontation between the findings obtained through the interviews and the corresponding literature. The research obeyed the ethic precepts preconized by the Resolution 466/12 of the National Council of Health, being approved on 18/06/2013, under the CAEE 14725013.0.0000.5188. The storage of the material collected will keep under supervision of the Program of Post-Graduation in Nursing of the Federal University of Paraíba (PPGEnf/UFPB).The discussion groups of ICT, as it was seen that such strategy promotes the recuperation of the processes of natural socialization that constitutes the human life, passing on directly to processes of inclusion, social rehabilitation, empowering and awakening of the resilience of the people who participate of the discussion groups. In the speeches, the female contributors reveal yet that changes in the self-esteem happened, so that in the ICT the people are encouraged to give new meaning to their suffering, empowering the rescue of the citizenship and of the autonomy. The mothers of disabled children revealed that during the discussion groups of ICT they had the chance to reflect about their lives, allowing changes in their quotidian representing, improvement in quality of their lives, promotion of mental health and prevention of psychological illnesses. In this conjuncture, the group of ICT that was formed in the ADAT, rescued values and slept potentialities, that many mothers who participated thought they didn t have, allowing them to wake up for a dynamic of reflection and learning which has no end, but rediscovers itself day after day.